An Online Doctorate for Researching Professionals - Ajayi, Tolulope (Journal of Interdisciplinary Studies in Education, 2020)
An Online Doctorate for Researching Professionals was written with the view of using new perspective in expanding the horizon of PhD students in higher education. The authors considered the development of online programs to meet the needs of the working professionals. This became necessary because the traditional PhD programs in education was not enough to meet the desires of the working professionals in combining the furthering of their education and  carrying out applied research skills with continuing full-time employment. The authors presented their model that focused on an online professional doctorate program which combined theory research and practice.